Seroepidemiology of Dengue Viral Infection in Peshawar - Pordil Khan, Mehwish Zafar, Ayesha Muneer, Aizaz Afridi, Muhammad Bilal, Syed Luqman Shuaib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dengue viral infection is the most prevalent infection particularly in the months of September to December in different region of Khyber Pakhtunkhwa. The aim of this study was to determine the prevalence of dengue viral infection in district Peshawar. Methods: A cross-sectional study was conducted and recruited two hundred suspected dengue viral infected patients. Blood were collected for diagnosis of dengue viral infection through immunochromatograpy technique. All the collected data analyzed through Microsoft Excel 2020. Results: A total of 200 suspected dengue viral infected patients participated. Among total, 59.5% were male and 40.5% were female patients. Out of total, 61 were found positive through NS-1 strips. IgG antibodies were more found in male than female. Whereas, IgM antibodies were more prevalent found in female patients. Conclusion: Overall, the prevalence of dengue viral infection is more in our region. The prevalence of dengue viral infection is greater in male patients as compared to female patients. It is important to arrange different prevention programs including seminars, workshops and conference throughout the district. Implementation of control and surveillance programs are highly essential to determine regarding the dengue level. Health policy makers need to pay attention towards the dengue disease and to provide different training session to health care providers and physician. Keywords: Dengue viral infection, Sero-prevalence, Epidemiology